Collaborative Performance and Swift Trust in Tourism Industry of Thailand: Role of Big Data Analytics Capability and External Supply Chain Management - Chayanan Kerdpitak; Sudawan Somjai; Natnaporn Aeknarajindawat; Chairit Thongrawd (International Journal of Supply Chain Management, 2019)
Building trust among different stakeholders of the business and collaborative performance are two most desired organizational outcomes. Such across the board relations largely based on big data exists about these relationships which help to sort out the conflicts. Through the very same big data, manufacturing industry can also look after its external supply chain management practices too. This study has checked the impact of Big Data Analytics Capability (BDAC) on swift trust and collaborative performance in Thailand’s manufacturing sector. Moreover, study has also analyzed the mediating role of external supply chain management in relationship between BDAC and swift trust and BDAC and collaborative performance. Data has been collected from managerial level employees of 39 manufacturing firms of Thailand equipped with big data capability. Questionnaire based data was then analyzed through SPSS and AMOS. BDAC was reflected as a significant predictor of swift trust and collaborative performance in results. Indirect role of external supply chain management was also flagged significant in results. This study is novel due to inclusion of external supply chain management as mediator and it will have its implications for manufacturing sector which can improve their collaborative performance through BDAC driven supply chain management.